The effect of a mobile application on the foot care of individuals with type 2 diabetes: A randomised controlled study - Dincer, Berna; Bahcecik, Nefise; Bahçecik, Ayşe Nefise (Sage Publications Ltd, 2021)
Objective: This study aimed to develop an animation-supported Mobile Diabetic Foot Care Education (M-DFCE) application for use by individuals with type 2 diabetes and identify its effects on knowledge, self-efficacy and foot care behaviour. Design: Randomised, controlled experimental study. Setting and Method: The study was carried out between October 2016 and September 2017. The sample consisted of 130 individuals with diabetes (65 in the experimental group and 65 in the control group). The experimental group received M-DFCE. Data were collected using the Patient Assessment Form, the Diabetes Foot Knowledge Questionnaire, the Diabetic Foot Care Self-Efficacy Scale and the Foot Self-Care Behaviour Scale. Differences between the groups were examined using Student's t, Mann-Whitney U, Wilcoxon Signed Rank and Paired Sample tests. Results: Although there was no difference between the groups at initial evaluation, individuals in the experimental group who received animation-supported M-DFCE had significantly higher knowledge, self-efficacy and foot care behaviour levels than the control group. Conclusion: The animation-supported mobile application developed for foot care education was effective in increasing the individuals' knowledge, self-efficacy and behaviour with respect to foot care.
Keywords: diabetic foot; mobile application; patient education; type 2 diabetes